Avaliação em larga escala na educação básica, Prova Brasil, em perspectiva da gestão democrática: um estudo a partir da Associação de Municípios do Vale do Rio dos Sinos e Município de São Leopoldo - RS - Andrade, Alenis Cleusa de (Universidade do Vale do Rio dos Sinos, 2011)
The study discusses the large-scale evaluation as a subsidiary of formulating educational policies facing mechanisms of democratic management contained in the municipal educational systems. The objectives of the study have as principle the confluence of that democratic strategies management in education contribute to overcoming situations started by large-scale evaluation and educational policies, consisting in identifying and analyzing indicators of democratic governance contained in the laws of the Municipal System of Education and the performance of students in municipal education systems, in Brazil Test, at elementary school. The focus is on the cities of the Association of Municipalities of Vale do Rio dos Sinos, which chose to create laws of Municipal Education Systems, specifically situating Sao Leopoldo as empirical focus, considering this city opted for the democratic management of education. The study describes how is the application process of Brazil Test and movements caused by this process on educational institutions. It points out some of the actions initiated by the Education Development Plan School, called PDE School, for schools that were below the national average in large-scale evaluation. The methodology make possible the articulation between different aspects of the investigation, by collecting data in Public Schools of Education, City Department of Education, State Education Department, through semi-structured interviews for agents involved in each area and consultations with official documents. The study reveals that Sao Leopoldo showed made advances in the democratic management, by the indicators, however, it showed reproductive characteristics. In the process of execution of Brazil Test was found a great complexity involved, where several actors began to intervene in school life following different temporalities. The intervention and temporalities led to an articulation in school management and to prepare to receive the application of Brazil Test, at the 2009 edition. The performance of the planning and decentralized execution of actions, started by PDE School, resulted in difficulties to be overcome by education systems, considering the absence of processes effectively participative and democratic in school ambit. It was evident a lack of educational policies that include interaction between the different municipal departments, educational institutions and higher instances in attendance to communities in disadvantaged social contexts.
Keywords: Avaliação em larga escala; Políticas educacionais; Gestão democrática; Large-scale evaluation; Educational policies; Democratic management; ACCNPQ::Ciências Humanas::Educação